The Effect of Index Card Match Strategy on Students' Vocabulary Mastery ( A Study at the Tenth Grade Students' SMA Negeri 1 Sitahuis 2017/2018 Academic year) - Noperto Tulus. P Tobing (JURNAL LINER (Language Intelligence and Educational Research), 2018)
The purpose of this research is to find out: 1) the application of index card match. 2) the extent of the students’ vocabulary mastery before and after using index card match. 3) whether there is any significant effect of index card match on students’ vocabulary mastery at the tenth grade students of SMA Negeri 1Sitahuis. Method of the ruler was the experimental. The population of this research was all of the tenth grade students of SMA Negeri 1 Sitahuis. It consist 100 students. Sistematic sampling technique was uses to get a sample it consist33 students. The technique for collecting data by observation sheet and giving test. The result mean score of the application of index card match was 3,43 it was “very good”.Value before using index card match was 58.69, it was categorized “enough”. While the mean score of the students’ vocabulary mastery after using index card match was 74.15, it was categorized “good”. The result of ttest was 10.62 and ttable was 2.04It means that there is a significant effect of using index card match on students’ vocabulary mastery at the tenth grade students of SMA Negeri 1 Sitahuis. Keyword: Index Card Match, Vocabulary Mastery